Slang In The Film Deadpool (2016): Sociolinguistics Study - Cipta Yudistira Ardira; Ervina CM Simatupang (Universitas Nahdlatul Wathan Mataram, 2026)
This study analyzes the use of slang in the film Deadpool (2016) from a sociolinguistic perspective, focusing on how informal language portrays character identity and social meaning. The purpose of this study is to identify the different types of slang used by Wade Wilson (Deadpool) and examine how these slang functions sociolinguistically in the film's dialogue. A qualitative descriptive method is applied using the film and its official transcripts as the primary data sources. A total of nine slang expressions spoken by the main character were collected through documentation and note-taking techniques, selected based on the criteria of containing standard, community, taboo, fresh and creative, acronym, and borrowed slang elements relevant to sociolinguistic analysis. The data were validated through triangulation of theory to ensure accuracy in classification and interpretation. The results show that Deadpool often uses innovative and inappropriate expressions to convey comedy, sarcasm, and emotional intensity, thus reinforcing his rebellious and humorous persona. This study demonstrates that slang in audiovisual media functions as a sociolinguistic phenomenon, fostering character development and narrative engagement, and reflecting group identity and social dynamics. By providing insight into the relationship between informal language and sociocultural expressions in popular media, this study contributes to sociolinguistic studies and offers a reference for further research on sociolinguistics.